Interest rate rules and monetary targeting: What are the links? - Christina Gerberding; Franz Seitz; Andreas Worms (Research On Money in the Economy (ROME), 2009)
The paper derives the monetary policy reaction function implied by money growth targeting. It consists of an interest rate response to deviations of the inflation rate from target, to the change in the output gap, to money demand shocks and to the lagged interest rate. We show that this type of inertial interest rate rule characterises the Bundesbank's monetary policy from 1979 to 1998 quite well. This result is robust to the use of real-time or ex post data. The main lesson is that, in addition to anchoring long term inflation expectations, monetary targeting introduces inertia and history-dependence into the monetary policy rule. This is advantageous when private agents have forward-looking expectations and when the level of the output gap is subject to persistent measurement errors.
Keywords: E43; E52; E58; 330; Monetary policy; Taylor rule; monetary growth targets; history dependence